Determinants of outcome behaviors of alcoholics after treatment and rehabilitation (Trinidad and Tobago) - Igwe, Benjamin O. (1988)
The study sought to determine the social and psychological factors that facilitated or hindered the various behavioral outcomes observed among alcoholics who have undergone treatment and rehabilitation in Trinidad and Tobago. The study involved 451 alcoholics discharged from the Substance Abuse Prevention and Treatment Centre, Caura Hospital. These alcoholics were followed-up at 4 and 8 months after their release from the hospital. The instruments employed in data collection were an interview schedule and a Jenkins Activity Survey questionnaire. The alcoholics' outcome behaviors were categorized as (a) abstinent, (b) controlled drinking, and (c) problem drinking, The X2 test was used in the univariate analysis of the relationship between the independent variables and outcome behaviors. Of the 42 independent variables employed in this study, 34 were found to be significant at 4 months and 31 at 8 months. The multiviriate analysis using the logistic multiple regression technique resulted in 2 predictive equations of behavioral outcomes for 4 and 8 months respectively. The predictive variables of outcome behavior at 4 months were: 1. Religion 2. Willingness or otherwise te recommend alcohol to friends 3. Friends' use/non-use of alcohol 4. Health personnel visit 5. Personality type Those variables that predicted behavioral outcomes at 8 months were: 1. Friends' use/non-use of alcohol 2. Health personnel visit 3. Ethnicity 4. Friends' orientation to alcohol Computation results show that 9 subjects out of every 10 who possess the predictive characteristics would be abstinent at 3 and 8 months respectively. Friends' use/non-use of alcohol and health personnel visit were considered the most important predictive variables because of their consistent presence at the 4 and 8 months equations, and partly because of their high abstinence odds ration. These variables can find utility as indicators in clinical and community settings for cost-effective program planning and evaluation.